1996
DOI: 10.1093/oxfordjournals.ndt.a027260
|View full text |Cite
|
Sign up to set email alerts
|

Economic appraisal of maintenance parenteral iron administration in treatment of anaemia in chronic haemodialysis patients

Abstract: Iron deficiency is very common in our haemodialysis population, especially in those patients receiving rHuEpo. A carefully monitored regimen of maintenance parenteral iron is a safe, effective, and economically favourable means of iron supplementation in patients with insufficient iron stores on maximum tolerated oral supplements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 0 publications
4
42
0
1
Order By: Relevance
“…The possibility that some patients could be treated with intravenous iron alone or that appropriate intravenous iron replacement may delay initiation or reduce the dosage of ESA could improve care and reduce costs. 44,45 Safety concerns with ESA raised by recent clinical trials, 46 -48 which led to a Food and Drug Administration warning in their package insert, further make the case for appropriate intravenous iron therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that some patients could be treated with intravenous iron alone or that appropriate intravenous iron replacement may delay initiation or reduce the dosage of ESA could improve care and reduce costs. 44,45 Safety concerns with ESA raised by recent clinical trials, 46 -48 which led to a Food and Drug Administration warning in their package insert, further make the case for appropriate intravenous iron therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts to maintain the hematocrit value by administering iron preparations and to decrease the consumption volume of erythropoietin preparations have been made from the pharmacoeconomic viewpoint in U.S.A. and Europe. [8][9][10] Most recently, even in Japan, a physicians' research group has reported that a small dose of iron preparations resulted in a 30% reduction of erythropoietin consumption for one year in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States and elsewhere, parenteral iron injections are advocated as the preferred route for anemia correction in chronic renal failure either alone or in combination with recombinant erythropoietin [12, 13, 14, 15, 16, 17]. When administered in combination with erythropoietin, parenteral iron injections purportedly enhance the response to erythropoietin, and consequently erythropoietin requirements may decline, resulting in substantial short-term cost savings [8, 13, 15].…”
Section: Indicationsmentioning
confidence: 99%
“…When administered in combination with erythropoietin, parenteral iron injections purportedly enhance the response to erythropoietin, and consequently erythropoietin requirements may decline, resulting in substantial short-term cost savings [8, 13, 15]. …”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation